2009
DOI: 10.2147/dhps.s4334
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of NSAID-related upper gastrointestinal toxicity: a meta-analysis of traditional NSAIDs with gastroprotection and COX-2 inhibitors

Abstract: Background:Traditional NSAIDs (tNSAIDs) and COX-2 inhibitors (COX-2s) are important agents for the treatment of a variety or arthritic conditions. The purpose of this study was to systematically review the effectiveness of misoprostol, H2-receptor antagonists (H2RAs), and proton pump inhibitors (PPIs) for the prevention of tNSAID related upper gastrointestinal (GI) toxicity, and to review the upper gastrointestinal (GI) safety of COX-2s.Methods:An extensive literature search was performed to identify randomize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
47
1
11

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(59 citation statements)
references
References 123 publications
0
47
1
11
Order By: Relevance
“…In this scenario, the TEP conditionally recommends the use of tramadol, duloxetine, or intraarticular hyaluronan injections. If the patient has a history of a symptomatic or complicated upper GI ulcer but has not had an upper GI bleed in the past year and the practitioner chooses to use an oral NSAID, the TEP strongly recommends using either a cyclooxygenase 2 (COX-2) selective inhibitor or a nonselective NSAID in combination with a proton-pump inhibitor; there was no preference expressed between these choices (29). In the clinical scenario where the above patient has had an upper GI bleed within the past year and the practitioner still chooses to use an oral NSAID, the TEP strongly recommends using a COX-2 selective inhibitor in combination with a proton-pump inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“…In this scenario, the TEP conditionally recommends the use of tramadol, duloxetine, or intraarticular hyaluronan injections. If the patient has a history of a symptomatic or complicated upper GI ulcer but has not had an upper GI bleed in the past year and the practitioner chooses to use an oral NSAID, the TEP strongly recommends using either a cyclooxygenase 2 (COX-2) selective inhibitor or a nonselective NSAID in combination with a proton-pump inhibitor; there was no preference expressed between these choices (29). In the clinical scenario where the above patient has had an upper GI bleed within the past year and the practitioner still chooses to use an oral NSAID, the TEP strongly recommends using a COX-2 selective inhibitor in combination with a proton-pump inhibitor.…”
Section: Resultsmentioning
confidence: 99%
“…46 Nevertheless, the preference for preventive strategies changed after warnings for an increased cardiovascular risk related to coxibs were released by regulatory agencies. 47 Although the risk of UGI complications with rofecoxib used to be higher than with celecoxib 48 , in a stratified analysis the estimate of nsNSAIDs plus GPAs compared to coxibs without rofecoxib after 2004 (i.e. celecoxib, etoricoxib, valdecoxib and lumiracoxib only) did not differ from the estimate including rofecoxib (before withdrawal).…”
Section: Discussionmentioning
confidence: 95%
“…59 A meta-analysis also showed that the use of COX-2-selective inhibitors results in significantly lower rates of gastroduodenal ulcers and their complications than the use of ns-NSAIDs does. 60 As for the lower GI tract, the CONDOR trial showed that the proportion of patients with clinically significant events throughout the GI tract was significantly greater in patients taking diclofenac in combination with omeprazole than in those taking celecoxib.…”
Section: Gastrointestinal Risks Of Nonsteroidal Anti-inflammatory Drugsmentioning
confidence: 99%